Nigrisagitta distichus, a new genus and species of Discocephalini from Venezuela (Hemiptera, Pentatomidae, Discocephalinae) - Rosso, Pedro; Campos, Luiz Alexandre (Zootaxa, 2017)
Nigrisagitta distichus Rosso & Campos, gen. n. and sp. n. is proposed based on morphological characters. The new genus can be differentiated from other broadheaded discocephalines by the shape of the bucculae and scutellum, the dorso-ventrally compressed pygophore, the shape of the male segment X, the lack of ring sclerites and the proximal narrowing of the ductus recptaculi in females.